2015
DOI: 10.1007/s00428-015-1806-8
|View full text |Cite
|
Sign up to set email alerts
|

High proliferation index, as determined by immunohistochemical expression of Aurora kinase B and geminin, indicates poor prognosis in neuroblastomas

Abstract: Expression profile analysis of cell cycle biomarkers provides a powerful index of the proliferative state of tumors, which is linked to disease aggressiveness. We investigated the impact of the biomarkers of S-G2-M phases of cell cycle, Aurora kinase B (AURKB) and geminin (GMNN), on disease progression in neuroblastomas. The expression of AURKB and GMNN was studied by immunostaining 84 neuroblastomas. A proliferation index (PI) was obtained on scanned immunostained slides using image analysis software. The med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Our results were similar to previous studies, which found that AURKB was closely correlated with the prognosis, invasiveness, chemoresistance of various tumors. [7][8][9][10][11] Based on these results, we considered that AURKB could function as a novel oncogene and become a potential therapeutic target in GC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results were similar to previous studies, which found that AURKB was closely correlated with the prognosis, invasiveness, chemoresistance of various tumors. [7][8][9][10][11] Based on these results, we considered that AURKB could function as a novel oncogene and become a potential therapeutic target in GC.…”
Section: Discussionmentioning
confidence: 99%
“… 6 Overexpression or amplification of AURKB is usually detected in human cancers, including breast cancer, 7 ovarian cancer, 8 gastric/gastrointestinal cancer and other tumors, 9 , 10 and is proved to be related to poor prognosis. 11 Therefore, AURKB has become a promising therapeutic target in tumors. Some researchers found that high expression of AURKB was associated with the improved overall survival in GC, 12 however, others considered that inhibition of AURKB reduced GC cell viability and increased the sensitivity of resistant GC cell to cisplatin.…”
Section: Introductionmentioning
confidence: 99%
“…Loss of AURKB activity could override spindle assembly checkpoint (SAC) through premature removal of SAC proteins from the kinetochore [7], which leads to defect of chromosome segregation and conformation of polyploidy. Overexpression or amplification of Aurora kinases is generally detected in amount of human cancers, such as breast cancer [8–11], ovarian cancer [1214], gastric/gastrointestinal cancer [15, 16] and other tumors [11, 1733] (Table 1) and is associated with the poor prognosis [8, 34, 35]. Thus, Aurora kinases become promising therapeutic targets and numerous AKIs have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal Aurora A expression also contributes to esophageal cancer development and cisplatin resistance [ 30 , 31 ]. The scientific literature indicates that high levels of Aurora A kinase are associated with advanced clinical stage and poor prognosis in several cancers [ 32 36 ]. Additionally, Aurora B overexpression is associated with acute myeloid leukemia [ 37 ] and colorectal cancer [ 38 ].…”
Section: Resultsmentioning
confidence: 99%